2011
DOI: 10.4314/wajm.v29i5.68249
|View full text |Cite
|
Sign up to set email alerts
|

Management of Febrile Neutropenia in Patients receiving Chemotherapy for Solid Tumors: A Retrospective Study of Twenty Cases from the Radiotherapy Centre, Accra, Ghana

Abstract: Gestion des neutropénies fébriles chez les patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(35 reference statements)
2
6
0
Order By: Relevance
“…Mortality within 90 days of starting chemotherapy among cancer patients in the current study was found to be 12% and was similar to 11% that was reported by Kudere et al from the United States among cancer patients on therapy in 2006 and slightly higher than 8% which has currently being reported from South Africa [8,15]. Additionally, similar mortality was reported in the study done in West Africa 8 years ago which reported the mortality of 10% [16].…”
Section: Discussionsupporting
confidence: 90%
“…Mortality within 90 days of starting chemotherapy among cancer patients in the current study was found to be 12% and was similar to 11% that was reported by Kudere et al from the United States among cancer patients on therapy in 2006 and slightly higher than 8% which has currently being reported from South Africa [8,15]. Additionally, similar mortality was reported in the study done in West Africa 8 years ago which reported the mortality of 10% [16].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the mortality was significantly high compared to 7.2% reported by the International Agency for Research on Cancer from Sub-Saharan Africa in the global cancer statistics of 2012 [ 15 ]. Additionally, similar mortality was reported in the study done in West Africa 8 years ago which reported the mortality of 10% [ 16 ]. Low functional status due to cancer itself and the toxicity brought by the therapy collectively compromise the health of the patients and might lead to high mortality observed after therapy initiation in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…15,[17][18][19] The median of the ANC (193 x 10 3 ) varies considerably between studies, being reported lower in some cases, as in the study of Düzenli (100 x 10 3 ), and greater in others, as in the Vanderpuye study (200 x 10 3 ). 18,20 Severe neutropenia (<200 x 10 3 ANC) was present in 19.3% events, lower than the study of Vathana et al, where it appeared in 44.4% laboratory findings. 21 Blood culture collection, although subpar according to current treatment guidelines, 8 is comparable with international and national studies, where it has varied from 9.4% to 26%.…”
Section: Discussionmentioning
confidence: 68%